(untitled) (Teología, 2023)
The present article tries to bring closer to the reading of the work The truth will make them free, that the Faculty of Theology of the Pontifical University of Catholic in Argentina has carried out at the request of the Argentine Episcopal Conference. This monumental work that involved more than thirty authors and required five years of work, has its history and is presented as a challenging and complex text. The central theme revolves around the Catholic Church in the spiral of violence in Argentina between 1966 and 1983. The sensitivity caused by this tragic stage in Argentine history, in which so many people have died, victims of the actions of guerrilla groups such as of State Terrorism systematically established by the Armed Forces, has had the Catholic Church, in all its levels, as one of its main actors. Although the studies on this subject are innumerable and probably incomprehensible for several decades now, the Catholic Church as an institution Êºhad and ÊºleÊº owed the entire Argentine society ÊºsomeÊº to take a position on the facts, through a serious, reflective study and self-critical of the place that implicated the entire Church in this spiral of violence. The declassification of the ecclesiastical Archives in various levels of government within the period studied, is one of the contributions that has enabled a critical rereading of events, institutions and people, particularly the Argentine Episcopal Conference itself. A work of this caliber and magnitude justifies an Êºapproach to readingÊº. We have tried following some options through two paths: a list of thematic axes (1-4), and a selection of guide texts (5) that serve as a stimulus to readers who may perhaps feel attracted to go through the study in more depth and Analysis of the work.